2007
DOI: 10.1021/ac0614285
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Sensing on a Modular Chip Containing a Single-Ion Channel

Abstract: Engineered protein channels have many potential applications in biosensing at the single molecule level. A future generation of biosensor could be an array of target-specific ion channels, where each protein pore acts as a sensor element. An important step toward this goal is to create a portable, durable, single protein channel-integrated chip device. Here we report a versatile, modular chip that contains a single ion channel for single molecular biosensing. The core of the device is a long-lived lipid membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 42 publications
0
77
1
Order By: Relevance
“…This lifetime was longer than that (several hours) of BLMs formed in conventional μm-scale apertures. 34 As shown in Fig. 3(d), gramicidin channel activities were clearly seen even 16 h after membrane formation, demonstrating the long-lasting functionality and stability of the present BLMs.…”
Section: Blms Spanned Over Anodic Porous Aluminamentioning
confidence: 52%
See 2 more Smart Citations
“…This lifetime was longer than that (several hours) of BLMs formed in conventional μm-scale apertures. 34 As shown in Fig. 3(d), gramicidin channel activities were clearly seen even 16 h after membrane formation, demonstrating the long-lasting functionality and stability of the present BLMs.…”
Section: Blms Spanned Over Anodic Porous Aluminamentioning
confidence: 52%
“…Thus the present BLMs could withstand a much higher voltage than the breakdown voltage (~220 -330 mV) reported for BLMs in apertures of 50 -100 μm. [32][33][34] Considering that the present BLMs have a total membrane size of ~75 μm, much higher BLM stability was achieved by supporting large membrane area with a nano-mesh structure of the porous alumina films. The membrane lifetime, defined as the duration for which BLMs retained resistance higher than 1 GΩ, was 16 -30 h (n = 2) with and without gramicidin channels.…”
Section: Blms Spanned Over Anodic Porous Aluminamentioning
confidence: 95%
See 1 more Smart Citation
“…Recent progress has been made by encapsulating planar bilayers in agarose gels. 35,36 It has been demonstrated that membranes with embedded proteins could be stored for weeks and regain their function after rehydration. Similarly, hydrogels have been used to protect planar bilayers.…”
Section: Protective Overcoatingsmentioning
confidence: 99%
“…A great deal of skill and practice is necessary in order to acquire practical data from these channel recordings meaning that although the information acquired is extremely useful, the labour is laborious and frustrating. Thus several proposals have been made for the construction of durable bilayers [1][2][3][4][5]. We have developed a practical method to produce such durable bilayers for channel measurements.…”
Section: Introductionmentioning
confidence: 99%